STIMULAREA ACTIVITĂŢILOR DE ÎNVĂŢARE PRIN EVALUARE - USM ADMIN (Moldova State University, 2011)
The assessment is involved in every moment of teaching and is an important component of the educational process. Chosen and applied correctly, the evaluative strategies effectively contribute to stimulating learning activities.